2022
DOI: 10.7759/cureus.26183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical Student Participation in Student-Run Clinics on Education, Residency Selection, and Patient Care: A Review of Selected Articles

Abstract: Student-run clinics (SRCs) are becoming increasingly popular at medical schools in the United States. These clinics have provided a variety of benefits, including serving disadvantaged populations and providing early clinical exposure for students. There has been no consensus on the impact of SRCs on medical education, specialty selection, and patient care. This review provides a thorough overview of student and patient outcomes as a function of medical students volunteering at SRCs. We queried PubMed for orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Sixteen articles reported students developed an increased understanding of patient's perspectives and experiences by engaging with the public through their education 4,14–16,18–20,22,23,25–29,31,32 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen articles reported students developed an increased understanding of patient's perspectives and experiences by engaging with the public through their education 4,14–16,18–20,22,23,25–29,31,32 …”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles reported that when the public interacted with healthcare students it resulted in increased trust between the public and healthcare providers 4,14–17,19,20,23,27,28,32 . These interactions also improved patient satisfaction 4,14–17,23,26,27 and improved communication between healthcare providers and the public 16,17,19,20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations